KPK’s Performance Dynamics in Combating Corruption After the 2019 Revision of the KPK Law - Rahmad Prasetyo; Faisal Santiago (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Corruption is a serious crime that has a significant impact on the government, the economy, and public welfare. The Corruption Eradication Commission (KPK), an independent organization charged with combating corruption, plays a crucial role in the Indonesian legal system and is empowered to carry out investigations, inquiries, and prosecutions against corruption crimes to uphold the supremacy of the law and create a clean government. However, along the way, the KPK's performance has experienced various challenges, both regulation, politics, and technicalities in carrying out its duties. Changes in regulations, especially through the revision of Law Number 30 of 2002 enacted in 2019, are one of the factors that influence the effectiveness of this institution in carrying out its duties. This study strives to analyze the performance of the KPK in enforcing the law on corruption crimes in Indonesia. The main focus of this study includes an evaluation of the effectiveness of the KPK in handling corruption cases, the challenges faced, and strategies that can be applied to improve the performance of this institution. The methods used in this study are normative and empirical juridical methods. The examination of various laws and regulations applying normative legal approaches governing the eradication of corruption, and investigating official documents such as the KPK's annual report. Meanwhile, the empirical approach is carried out by analyzing case data handled by the KPK. The research results are expected to provide an overview of the effectiveness of the KPK in enforcing the law against criminal acts of corruption and provide constructive recommendations for efforts to eradicate corruption in Indonesia.